FUNGSI PANTUN MELAYU TRADISIONAL DILIHAT DARI PERSPEKTIF BUDAYA DAN ALAM PEMIKIRAN MASYARAKAT MELAYU - Cho Min Sung; Mat Zaid bin Hussein (Universitas Andalas, 2020)
Pantun is a group of rhymed verses that support the beauty and finesse, which embody a strong and influential idea. Traditional Malay pantun works in almost every activity of the life of the Malay community, including expressing the values and culture of a tradition, questions of love and affection, concepts of humour as well as religious values. It also serves to convey the ideas and thoughts of its speakers and reflect the lives of its creator. In the creation of Malay pantun, all the experiences, views and philosophies of life conveyed in it use the nature background as a hint or meaning. The use of such elements reflects the intimate and bonded connection of the Malay community with the elements of nature around them. The creation of pantun often uses words related to the elements of nature that are present in the environment of the Malay community, especially in the form of symbolism or those imagining a variety of symbolic images that can exemplify the aesthetic value besides the meaning and profound message. The privileges and strengths of the Malay pantun can be seen in the use of certain symbols chosen based on the perception and worldview of the life of the Malay community and on the semantic relationship between hint and meaning. Keywords: Malay pantun, Malay community, function of pantun, nature background